Profil Kemampuan Pemahaman Konsep Bangun Ruang pada Siswa Kelas V di SDN 09 Rangkang (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to describe the profile of students' conceptual understanding ability in spatial geometry for fifth-grade students at SDN 09 Rangkang, Bengkayang. This research is a descriptive study with a qualitative approach. The subjects were the class teacher and ten students (five boys and five girls). Data were collected through observation, interviews, and documentation. The data analysis techniques consisted of data reduction, data presentation, and conclusion drawing. Data validity was ensured through prolonged engagement and triangulation. The results showed that students' understanding of the concepts of volume and nets of cubes and rectangular prisms can be categorized as good.